Things Fall Apart - Achebe, Chinua (Heinemann Educational Books Ltd, 1958)
This expanded edition of Chinua Achebe's first novel portrays the collision of African and European cultures in an Igbo village. Okonkwo, a great man in Igbo traditional society, cannot adapt to the profound changes brought by the British conquest of Nigeria.
Keywords: Nigerian Literature - Colonialism - African cultures